Frailty in long‐term Dutch adult survivors of childhood acute myeloid leukaemia, neuroblastoma, and Wilms' tumour. Issue 1 (7th October 2020) - Verwaaijen, Emma J.; Corbijn, Daniëlle M.; van Hulst, Annelienke M.; Neggers, Sebastian J.C.M.M.; Boot, Annemieke M.; van den Heuvel‐Eibrink, Marry M.; Hartman, Annelies; Pluijm, Saskia M.F.
Abstract: Background: Several simultaneous impairments in physical ability may be an indication of frailty in adult survivors of childhood cancer (CCS). The aim of our study was to assess the occurrence of frailty and to explore potential determinants in a selected Dutch cohort of long‐term adult CCS. Methods: In this cross‐sectional study, we used data of 70 very long‐term CCS [median age 28.8 years (interquartile range: 23.9–34.6)] of acute myeloid leukaemia (AML) ( n  = 17), neuroblastoma (NBL) ( n  = 25), and Wilms' tumour (WT) ( n  = 28). Prefrailty and frailty were defined as having, respectively, 2 and ≥3 of the five following components: low relative lean body mass (by dual‐energy X‐ray absorptiometry less than −1.5 standard deviation, SD), self‐reported exhaustion (fatigue, exhaustion, or exertion related complaints), low energy expenditure (men: <383 kcal/week, and women: <270 kcal/week), slow walking speed (less than −2.0 SD on the 6‐min walk test), and weakness (hand grip strength less than −2.0 SD). Potential determinants of prefrailty and frailty (≥2 components), including treatment components, sociodemographic, and lifestyle factors, were evaluated using logistic regression analysis. Results: Respectively, 6.3% and 28.1% women and 5.3% and 26.3% men were classified as frail and prefrail. Six per cent of the AML, 8% of the NBL, and 3.6% of the WT CCS were frail. Forty‐one per cent of the AML, 28% of the NBL, and 17.9% of the WT CCS were prefrail. No significant associations were found between any of the investigated determinants and frailty or prefrailty. Conclusion: Our results confirm previous reports that CCS, in particular intensively treated, have a potential risk of (pre)frailty.